2020
DOI: 10.21147/j.issn.1000-9604.2020.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors in malignant lymphoma: Advances and perspectives

Abstract: Classical Hodgkin lymphoma (cHL) has been identified with universal genetic alterations of chromosome 9p24.1, which contains PD-L1/PD-L2 genes. The amplification of 9p24.1 is associated with the increased expression of PD-L1 and PD-L2 on RS cells, which promotes their immune evasion, and subsequently makes cHL sensitive to PD-1 blockade. Several PD-1 inhibitors have shown significant efficacies with overall response rate (ORR) of 70%−90% in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Anti-PD-1 antibodies have been approved for use in various solid tumors and lymphomas ( 7 ). A multicenter, single-arm, phase II trial of sintilimab to treat relapsed or refractory classical Hodgkin’s lymphoma (cHL) was carried out in China and showed that the overall response rate (ORR) was 80.4% ( 5 , 8 ).…”
Section: Pd-l1mentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-PD-1 antibodies have been approved for use in various solid tumors and lymphomas ( 7 ). A multicenter, single-arm, phase II trial of sintilimab to treat relapsed or refractory classical Hodgkin’s lymphoma (cHL) was carried out in China and showed that the overall response rate (ORR) was 80.4% ( 5 , 8 ).…”
Section: Pd-l1mentioning
confidence: 99%
“…The finished clinical trials are summarized in Table 1 and ongoing ones in Table 2 . Avelumab is a fully human IgG1 mAb that selectively blocks PD-L1 and enhances anti-tumor T-cell activity ( 7 ). A phase I study of avelumab demonstrated that ORR and complete response (CR) were 54.8% and 6.5%, respectively, in patients with relapse/refractory cHL who had suffered progression following stem cell transplantation (SCT) or SCT-ineligible ( 7 ).…”
Section: Pd-l1mentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) binds to CD80 (B7-1) or CD86 (B7-2) and decreases activity of T cells by interrupting CD28-mediated co-stimulatory signaling. Aberrant overexpression of programmed death ligands 1 and 2 (PD-L1, PD-L2) or T-cell immunoglobulin and mucin domain 3 (TIM3) on malignant cells induce T-cell impairment, exhaustion, and apoptosis [ 64 , 65 , 66 ]. With the approval of several immune checkpoint inhibitors for the treatment of diverse solid cancers, it is now evident that the original proof-of-concept of inhibition of cancer-induced immunosuppression successfully translated into clinical practice.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…In 2018, James P. Allison and Tasuku Honjo were awarded a Nobel Prize in Physiology and Medicine “for their discovery of cancer therapy by inhibition of negative immune regulation”. In hematologic malignancies, PD-1 blockade with nivolumab or pembrolizumab in R/R Hodgkin lymphoma became a flagship of immune checkpoint inhibition in lymphoproliferative disorders reaching ORR of 65% to 87% [ 66 ]. Curiously, in contrast to solid tumors and Hodgkin lymphoma, the implementation of checkpoint inhibitors into the treatment algorithms of NHL still remains a matter of investigation [ 68 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%